Interdependent = Compassionate? Compassionate and Self-Image Goals and Their Relationships With Interdependence in the United States and Japan - Niiya, Yu; Crocker, Jennifer (Frontiers in Psychology, 2019)
The pursuit of compassionate goals, which involves focusing on and attending to other people’s needs, has often been described as a defining characteristic of an interdependent self that prioritizes harmonious relationships over individual achievement. This research investigated whether compassionate goals can be empirically distinguished from various indices of interdependence and examined their correlations with interdependence in both American and Japanese adult samples. It further differentiated two types of self-image goals—the goals to appear warm and kind vs. the goals to appear competent and in control—and explored their relationships with interdependence. In Study 1, the 18-item scale showed a clear four-factor structure that distinguished (a) compassionate goals, (b) approach-worded likable self-image goals, (c) approach-worded competent self-image goals, and (d) avoidance-worded self-image goals. Study 2 confirmed the equivalence of the four-factor structure and the equivalence of factor loadings in the U.S. and Japan. Finally, Study 3 showed that the items of compassionate goals and those of various measures of interdependence loaded onto separate factors with only negligible cross-loadings. Study 3 further found that the indices of interdependence reflecting connection with others showed moderately positive correlations with compassionate goals whereas indices of interdependence reflecting conformity showed moderate correlations with likable, competent, and avoidant self-image goals, indicating that the pursuit of compassionate and self-image goals reflect different aspects of interdependence.